Research of diamond concentration in dicing blade effect by electroplating parameter. (October 2019) - Zhu, Xiaowei; Wang, Yongbao; Liu, Jianshuang; Wang, Zhan; Dong, Feng
Abstract: In order to study the effect factors of diamond concentration in Dicing Blade prepared by composite coating method, a uniform distribution diamond composite coatings was prepared by suspension and high-low speed interval agitation method on the aluminium alloy blade hub. The effects of suspension diamond content, stirring speed, current density, surface tension and solution temperature to diamond concentration in composite coatings were studied. And the result shows the concentration of diamond in the coating is proportional to the suspending content in electroplating solution, the suspending diamond content increases, and the concentration of diamond in the coating increases until reaching a saturation value. The diamond concentration of coatings is inversely proportional to the stirring speed of sand, and obtained maximum concentrations when current density is 2.0 A/dm2 and temperature is 50°C. The surface tension has little effect to the concentration of diamond in the coating layer.